Analysis of physicochemical, functional, and antioxidant properties of four different Indian seaweed species - Radheshyam B. Bajad; Meenatai G. Kamble; Sumit R. Gawai; Irshaan Syed; Mrinmoy Roy (Future Foods)
The present study aims to elucidate the nutritional, functional, flow, and antioxidant properties of Ulva fasciata, Ulva lactuca, Chaetomorpha linum, and Gracilaria edulis. The highest percentage of protein (24.26 %) in U. fasciata; fat (6.33 %) and total carbohydrates (46.39 %) in C. linum; crude fibre (8.67 %) in U. lactuca; ash (22.45 %) content in G. edulis was observed among the four-seaweed. The highest oil absorption capacity was found for C. linum (1.59 %), followed by G. edulis (1.21 %), U. lactuca (1.04 %), and U. fasciata (0.91 %). The water absorption capacity in U. fasciata (4.55 %) was observed to be the highest followed by C. linum (3.84 %), U. lactuca (3.78 %), and G. edulis (2.22 %). U. fasciata exhibited the highest solubility (35.83 ± 1.97 %) and emulsifying capacity (99.00 ± 0.00 %), while G. edulis showed the highest foaming capacity (75.00 ± 1.00 %). The angle of repose of G. edulis and C. linum powder showed excellent flowability than U. lactuca and U. fasciata. Carr's index and Hausner ratio showed that all seaweed samples were free-flowability, except for G. edulis and C. linum. The bulk density (0.71 g/cm3) and tapped density (0.85 g/cm3) of U. fasciata were observed to be the highest, whereas true density (1.11 g/cm3) was recorded highest in U. lactuca. The most increased antioxidant activity was found in G. edulis (65.90 %) followed by C. linum (53.01 %), U. lactuca (51.76 %), and U. fasciata (43.56 %). The total phenolic content (10.93 mg GAE/g) and flavonoid content (1.71 mg QE/g) were higher in U. fasciata. FTIR analysis detected the presence of amide, amino, hydroxyl, ester groups and it can conclude the presence of essential components such as proteins, amino acids, polysaccharides, and fat. Thus, the selected four marine seaweeds act as a good source of functional components and can be utilized for the development of functional food products such as bread, biscuits, cookies, tea, snacks, soups and beverages.